VARIATIONS IN WOOD DENSITY AND MECHANICAL PROPERTIES OF Manglietia conifera Dandy PLANTED IN NA RI, BAC KAN - Van Doan, Duong; Thi Thu Ha, Tran; Thi Kim Hue, Duong; Thi Yen, Trieu (Journal of Forestry Science and Technology, 2020)
The radial and axial variations in wood density and mechanical properties of 10-year-old Manglietia conifera Dandy planted at Na Ri district, Bac Kan province were investigated. Wood samples with dimesions of 20 ´ 20 ´ 320 mm (Radial ´ Tangential ´ Longitudinal) were collected from 10, 50, and 90% of the radial length from pith at 0.3, 1.3, 2.3, 3.3, and 4.3 m heights above the ground. The raidal variations from pith to bark and axial variations at different heights were investigated to clariy effect of radial and axial positions on wood density (WD) and mechnical properties of Manglietia conifera. The mean values of WD, modulus of rupture (MOR), and modulus of elasticity (MOE) at 10.71% moisture content were 0.45 g/cm3, 54.09 MPa, and 6.12 GPa, respectively. The mean values of WD, MOR, and MOE within tree of Manglietia conifera increased significantly from pith to bark, while those in axial direction changed very small and no statistical significance. WD had a positive linear relationship with both MOR (r = 0.71, p < 0.001) and MOE (r = 0.69, p < 0.001). This suggests that WD is a good indicator to predicting the mechanical properties of Manglietia conifera wood.